Citizen Security: Reflections and Further Work - Guzmán Filippi, Guillermo (Revista INVI, 1994)
This paper collects some of the ideas presented at the "V Taller de Coyuntura" as well as ideas by authors who have worked on this topic from a spatial viewpoint. The importance of urban an architectural intervention as prevention strategies is here stressed. The paper such strategies can be produced, the institutional structure and in a few words the city and the society we are building as potenciations of delinquency and citizen's insecurity. Finally, it proposes several actions to face this problem to reinforce civil society as an element of prevention, to potenciale the collective production of space, to re-value local space as a prevention place and give way for an institutional structure which would promote the co-responsibility for public space, all within a global plan to face the problem.